The Victorian Roots of the Current ANC Leadership Crisis. Issue 6 (1st November 2016) - Mangcu, Xolela
Abstract : This essay offers an alternative explanation for the authoritarian, elitist and corrupt culture that has gripped South Africa's ruling party over the past twenty years of democracy. While most explanations point to the ANC's hierarchical underground structure and the secretive culture of the South African Communist Party (SAC), this essay traces the alienation to the elitist Victorian culture of its early leadership. Even as they appealed to the working people to support the cause of African rights, these leaders saw themselves as a class apart because of their level of education and the citizenship rights they enjoyed in the Cape. The prerogative to speak for the people translated into a culture of entitlement to privileges that were not otherwise available to the rest of the people. This gave its post-apartheid presidents, particularly under Thabo Mbeki's rule, not only the prerogative to make political decisions for the people but also to discipline them when they went out of line. These leaders did not take kindly to being questioned about their corruption. The election of a little-educated Jacob Zuma was an attempt to correct for this elitism, but the new leader had learned too well the ways of the elite.